Patient specific bony and soft-tissue fibular reconstruction: Perforator virtual surgical planning technique - Mohammed Qaisi; Wu Zheng; Thaer Al Azzawi; James Murphy (Elsevier, 2022)
Recent development in Virtual Surgical Planning (VSP) allows for planning of both the bony and soft tissue reconstruction by incorporating skin paddle perforator planning to the 3D planning module. This study aims to describe the perforator planning technique and report on its intraoperative predictability. Methods: A retrospective chart review identified all cases of fibular free flap reconstruction in which VSP was used in combination with perforator soft tissue planning from 2016 to 2022. Data collection included the accuracy of perforator location based on VSP planning versus clinical insitu measurements. Results: Of 61 patients that underwent free flap reconstruction between 2016 and 2022, a total of 19 patients were identified to have undergone fibula free flap reconstruction with the aid of virtual surgical planning utilizing the perforator planning technique. The average number of fibular segments utilized per patient were 2.15. The mean size of the skin paddle harvested was 5.75 cm × 7.25 cm.The VSP planned perforator vessels were identified clinically in all patients. Exact measurement of the dopplerable skin perforator measured from the lateral malleolus were recorded in 8/19 patients. In the remaining 11 patients estimated data was recorded to indicate whether the perforator was located within 2 cm of the pre-planned VSP perforator location; All 11 perforators were identified within a 2 cm radius.In the 8 cases with exact measurements, the insitu clinical perforator measurements differed by a mean 0.55 cm from the predicted locations (range 0-1.8 cm). In 18/19 cases the perforator was reported to be at the same level or inferior to the predicted perforator location. The pearson correlation coefficient showed a strong correlation between virtual and intraoperative measurements r = 0.984; p < 0.001. Conclusion: The incorporation of perforator planning allows for predictable identification of skin perforators both virtually and intraoperatively. This in turn allows for predictable capturing of the skin paddle perforator within the desired fibular segment allowing for true patient specific bony and soft tissue reconstruction.